Betaine: A potent feed additive for amelioration of adverse effect of heat stress in livestock and poultry - S V SINGH; ADITYA D DESHPANDE; YALLAPPA M SOMAGOND (Indian Journal of Animal Sciences, 2022)
This review encapsulates the beneficial effects of dietary betaine in livestock and poultry to ameliorate the adverse effect of heat stress. Betaine (trimethylglycine) has its own functional, nutritional and physiological roles. It is widely used in feed formulations as feed additive in livestock and poultry feed to increase performance. Beet (Beta vulgaris) is the main source of commercially available betaine. Betaine’s molecular structure possesses N+ and COO-, so it acts as a zwitter ion. Main functions of betaine are as an osmolyte as well as a methyl group donor. These functions showed many valuable effects of dietary betaine to livestock and poultry. Betaine binds with water molecules in its hydration shell and prevents cellular dehydration. This function mainly helps to ameliorate heat stress in livestock and poultry. It is also used as growth promoter in pig farming. Betaine supplementation resulted in increased antioxidant enzyme levels to prevent cellular oxidative stress and ROS formation. Betaine supplementation increased milk yield as well as milk fat in lactating dairy animals. It also increased carcass quality and lean meat production by suppressing lipogenesis genes in meat animals. Also, betaine is stable, non-toxic, and a cost-effective feed additive. Therefore, it can be concluded that betaine is a potent feed additive for livestock and poultry farming.